2021
DOI: 10.1097/md.0000000000024751
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk stratification nomogram for predicting prognosis in bone metastatic breast cancer

Abstract: Bone metastasis seriously affects the survival of breast cancer. Therefore, the study aimed to explore the independent prognostic factors in bone metastatic breast cancer (BMBC) and to construct a prognostic nomogram that can accurately predict the survival of BMBC and strictly divide the patients into different risk stratification. Four thousand three hundred seventy six patients with BMBC from the surveillance, epidemiology, and end results database in 2010 to 2015 were collected and randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Through multivariate analysis, we identified independent risk factors for patients with BMBC. Previous studies have also shown that age, tumor size, tumor grade, and molecular subtype may be risk factors for MBC, which is consistent with the results of our study (21,(23)(24)(25). Our study indicates that pN stage, which reflects the status of the axillary lymph nodes, is an important independent Nomogram to predict the probability of bone metastasis in a patient with non-metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Through multivariate analysis, we identified independent risk factors for patients with BMBC. Previous studies have also shown that age, tumor size, tumor grade, and molecular subtype may be risk factors for MBC, which is consistent with the results of our study (21,(23)(24)(25). Our study indicates that pN stage, which reflects the status of the axillary lymph nodes, is an important independent Nomogram to predict the probability of bone metastasis in a patient with non-metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Nowadays, in order to predict the outcome and guide the clinical management, more and more researchers prefer to establish clinical prognosis models [ 9 , 10 ]. As a popular quantitative predictive tool, nomogram was usually used to predict the prognosis of cancer patients [ 7 , 11 , 12 ]. Recently, Mao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nomogram is a tool that can integrate various factors, such as clinical, pathological, demographic, and oncological factors, to predict medical events and has gained popularity in predicting the prognosis of cancer patients [12,13]. When it comes to intuitively estimating the survival rates of cancer patients, nomograms possess an advantage in terms of accuracy compared to the traditional TNM staging system [14].…”
Section: Introductionmentioning
confidence: 99%